2021
DOI: 10.2139/ssrn.3844430
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of the Link between Life Satisfaction and Job Satisfaction across Europe

Abstract: Work forms one of the important spheres of life and is one of the main determinants of subjective well-being in general and life satisfaction in particular (Argyle 2001;Sousa-Poza & Sousa-Poza 2000). The study aims to disclose the impact of work values and socio-demographic characteristics upon the link between life satisfaction and job satisfaction. The European Values Study 2008-2009 is used as dataset. The sample is limited to those who have jobs (28 653 cases). The results confirm findings from the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Of the papers documented in Table 2, no study aims to assess the influence of Decent Work components on SWB (the following studies only partially evaluate some components of Decent Work: Cerci and Dumludag, 2019;Karani and Mehta, 2022). On the other hand, most of the works in Table 2 address the relationship between job satisfaction and SWB (Ampofo et al, 2022;Bas ¸ol and Ç€ omlekçi, 2022;Karabati et al, 2019;Soboleva, 2021) measured through subjective aspects such as the perception of workers, thus limiting the identification of other variables that allow the establishment of public policies that promote better working conditions to positive influence SWB levels. Specifically for the variable leisure, which aims to assess the balance between work and leisure that a person has in their life (Rashmi and Kataria, 2021;Sprague et al, 2020), the study by Riquelme-Segura et al (2022) identified a significant negative influence between work-tofamily conflict and SWB, where the study only worked with women from Chile.…”
Section: Studies On Subjective Well-being and Decent Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the papers documented in Table 2, no study aims to assess the influence of Decent Work components on SWB (the following studies only partially evaluate some components of Decent Work: Cerci and Dumludag, 2019;Karani and Mehta, 2022). On the other hand, most of the works in Table 2 address the relationship between job satisfaction and SWB (Ampofo et al, 2022;Bas ¸ol and Ç€ omlekçi, 2022;Karabati et al, 2019;Soboleva, 2021) measured through subjective aspects such as the perception of workers, thus limiting the identification of other variables that allow the establishment of public policies that promote better working conditions to positive influence SWB levels. Specifically for the variable leisure, which aims to assess the balance between work and leisure that a person has in their life (Rashmi and Kataria, 2021;Sprague et al, 2020), the study by Riquelme-Segura et al (2022) identified a significant negative influence between work-tofamily conflict and SWB, where the study only worked with women from Chile.…”
Section: Studies On Subjective Well-being and Decent Workmentioning
confidence: 99%
“…, 2022; Başol and Çömlekçi, 2022; Karabati et al. , 2019; Soboleva, 2021), which is usually measured through subjective aspects such as the perception of workers, thus limiting the identification of other variables that allow the establishment of public policies that promote better working conditions to positive influence SWB levels.…”
Section: Studies On Subjective Well-being and Decent Workmentioning
confidence: 99%